2021
DOI: 10.1101/2021.11.09.467893
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insula dynorphin and kappa opioid receptor systems regulate alcohol drinking in a sex-specific manner in mice

Abstract: Alcohol use disorder is complex and multi-faceted, involving the engagement of multiple signaling systems across numerous brain regions to drive pathological behavior. Previous work has indicated that both the insular cortex and dynorphin (DYN)/Kappa opioid receptor (KOR) systems contribute to excessive alcohol use. More recently, we identified a microcircuit in the medial aspect of the insular cortex that signals through DYN/KOR. Here, we explored the role of insula DYN/KOR circuit elements on alcohol intake … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Furthermore, deletion of dynorphin within IC blocks escalated EtOH intake in mice (Pina et al, 2021). Interestingly, the number of aversive responses to EtOH was negatively correlated with the number of FLI+ cells within the anterior IC, although this difference did not quite reach statistical significance.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, deletion of dynorphin within IC blocks escalated EtOH intake in mice (Pina et al, 2021). Interestingly, the number of aversive responses to EtOH was negatively correlated with the number of FLI+ cells within the anterior IC, although this difference did not quite reach statistical significance.…”
Section: Discussionmentioning
confidence: 89%
“…Opioid signaling within this area of IC increases the positively hedonic “liking” response elicited by intraorally delivered sucrose solutions (Castro and Berridge, 2017) further demonstrating that neural adaptations within this subregion of IC may be critical for driving enhancements of hedonic responding to orally delivered stimuli. Furthermore, deletion of dynorphin within IC blocks escalated EtOH intake in mice (Pina et al, 2021). Interestingly, the number of aversive responses to EtOH was negatively correlated with the number of FLI+ cells within the anterior IC, although this difference did not quite reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Opioid signaling within this area of IC increases the positively hedonic “liking” response elicited by intraorally delivered sucrose solutions (Castro & Berridge, 2017) further demonstrating that neural adaptations within this subregion of IC may be critical for driving enhancements of hedonic responding to orally delivered stimuli. Furthermore, deletion of dynorphin within IC blocks escalated EtOH intake in mice (Pina et al, 2021). Interestingly, the number of aversive responses to EtOH was negatively correlated with the number of FLI+ cells within the anterior IC, although this difference did not quite reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…The insular cortex (or insula), is strongly involved in drug addiction (32)(33)(34), including AUD (35)(36)(37). Indeed, human functional imaging studies have demonstrated that alcohol cues trigger greater activity responses in the insula, in alcohol dependent subjects (38,39).…”
Section: Introductionmentioning
confidence: 99%